Maturity, Ripening of fruit and control of Penicillium spp. rottenness in ‘Fuji’ apples with the preharvest application of resistance inducers (Revista de Ciências Agroveterinárias, 2014)
Much of the postharvest losses in pomiculture is due to the occurrence of diseases, and blue mold is one of the main ones. This research aimed at assessing the effects of preharvest application of potassium phosphite and bioflavonoids+phosphite on the Penicillium spp. rottenness control and on the maturity and ripening of ‘Fuji’ apples. The variables assessed were the incidence and severity of Penicillium spp. rottenness, flesh firmness, texture, soluble solids content, titratable acidity, starch-iodine index, peel color, respiratory rate and ethylene production. The experiment was based on a randomized block design with four replications. The means were compared by Tukey’s test (p
Keywords: Blue mold; Incidence; Severity; Ripening.